Hubungan Depresi Terhadap Tingkat Kepatuhan dan Kualitas Hidup Pasien Sindrom Dispepsia di RSUP Dr. M. Djamil Padang - Bobbi Hemriyantton; Helmi Arifin; Arina Widya Murni (Jurnal Sains Farmasi & Klinis, 2017)
The objective of this study was to examine the correlation of depression, adherence, and quality of life in dyspepsia patient. Cross-sectional data were collected from 61 outpatient with dyspepsia at a special clinic in M. Djamil Hospital Padang. Patients were interviewed based on BDI II (Back Depression Inventory II) to assess depression, Morisky scale to assess adherence. Patient with BDI scores more than 12 was consulted to a special clinic of psychosomatic to diagnose for depression. Correlation between depression, adherence, and quality of life was analyzed with Spearman correlation. Coefficient correlation of depression and adherence was 0.272, while the correlation between depression and quality of life was 0.655. This finding demonstrates that there is a high correlation between depression and quality of life, while there is a low correlation between depression and adherence. Keywords: Depression, adherence, quality of life, dyspepsia.